2010
DOI: 10.1111/j.1708-8208.2010.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Implants after Alkali Heating Treatment with a [Zn(OH)4]2− Complex: Analysis of Interfacial Bond Strength Using Push‐Out Tests

Abstract: The obtained results suggest that biochemical bonding at the bone-implant interface, stimulated by the Zn(2+) ion release in combination with mechanical interlocking definitively improved the implant fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In the Zn-modified sample the surface morphology and the TF-XRD data were consistent with the results reported by previous work [9], and the surface is supposed to be the structure as illustrated in Fig. 5, based on reference 9.…”
Section: Comparison Between Zn-modification and Groove-formation Towasupporting
confidence: 79%
See 2 more Smart Citations
“…In the Zn-modified sample the surface morphology and the TF-XRD data were consistent with the results reported by previous work [9], and the surface is supposed to be the structure as illustrated in Fig. 5, based on reference 9.…”
Section: Comparison Between Zn-modification and Groove-formation Towasupporting
confidence: 79%
“…[7,8]. Alvarez, et al reported that the alkali heating treatment with a [Zn(OH) 4 ] 2-, called Zn-modification, was more effective on bone fixation than other processes [9]. From mentioned above, we can understand that a Zn-modification and a moderate topographic pattern contributed to better osseointegration.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…; Alvarez et al. ; Kokubo & Yamaguchi ), oxidised and ions incorporated titanium (Giannuzzi et al. ; Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to those of previous papers. Alvarez et al (2010) demonstrated that implants treated with a solution containing [Zn(OH) 4 ] 2− complex showed increased bone fixation compared with control groups. A Zn-containing α-tricalcium phosphate (αZnTCP) was shown to promote new bone formation (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%